A Drosophila Smyd4 homologue is a muscle-specific transcriptional modulator involved in development. - Thompson, E.C.; Travers, A.A. (PLoS ONE, 2008)
SET and MYND domain (Smyd) proteins are involved in the transcriptional regulation of cellular proliferation and development in vertebrates. However, the in vivo functions and mechanisms by which these proteins act are poorly understood.We have used biochemical and genetic approaches to study the role of a Smyd protein in Drosophila. We identified eleven Drosophila genes that encode Smyd proteins. CG14122 encodes a Smyd4 homologue that we have named dSmyd4. dSmyd4 repressed transcription and recruited class I histone deacetylases (HDACs). A region of dSmyd4 including the MYND domain interacted directly with approximately 150 amino acids at the N-termini of dHDAC1 and dHDAC3. dSmyd4 interacts selectively with Ebi, a component of the dHDAC3/SMRTER co-repressor complex. During embryogenesis dSmyd4 was expressed throughout the mesoderm, with highest levels in the somatic musculature. Muscle-specific RNAi against dSmyd4 resulted in depletion of the protein and lead to severe lethality. Eclosion is the final moulting stage of Drosophila development when adult flies escape from the pupal case. 80% of dSmyd4 knockdown flies were not able to eclose, resulting in late pupal lethality. However, many aspects of eclosion were still able to occur normally, indicating that dSmyd4 is likely to be involved in the development or function of adult muscle.Repression of transcription by dSmyd4 and the involvement of this protein in development suggests that aspects of Smyd protein function are conserved between vertebrates and invertebrates.